Mechanism of Payment for Labor (Eurasian Journal of History, Geography and Economics, 2022)
This article talks about the mechanism of payment for labor. The market mechanism of setting the level of payment for labor is based on the nature of the supply of labor resources and their demand in the labor market. In this matter, first of all, the decision taken by the person himself regarding the implementation of labor activity is important. If he intends to work, first of all, he should decide how much time he will be engaged in paid work and how much time he will devote to free time. Based on his decision, the person makes his demands to the employer in the labor market.